An analytical study of sustainable development and its obstacles in some Arab countries (Journal of Hama University, 2022)
The research aimed to shed light on the concept of sustainable development, identify its foundations, and justifications for its adoption, as well as clarifying the economic, social, and environmental obstacles to sustainable development in the Arab countries.The research relied on the data available in the reports prepared by specialized international organizations on the Arab countries.The research reached a set of results, the most important of which is the existence of economic, social and environmental obstacles that are interconnected, and constitute a clear challenge to some Arab countries, in their quest to achieve sustainable development, most notably:The high rate of population growth, the high rate of poverty, unemployment, the spread of illiteracy, especially among females, the widening of the gender gap, in addition to the scarcity of water in the Arab countries, the poor management of what is available from it, the problem of drought and desertification, and the pollution of groundwater, and the researcher suggested a number of recommendations It may contribute to addressing these obstacles if they are followed.